2017
DOI: 10.31237/osf.io/z32ru
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Putting Lewin’s Equation to the Test: Assessing the Person-Situation Interaction with the B5PS

Abstract: Lewin hypothesized in 1936 that behavior is a result of the person’s personality and the environment. This basic distinction of two factors influencing behavior led to the person- situation debate. The current study briefly reviews the debate with its major arguments and concepts, putting a special focus on the newly developed concept of situation perception as a substitute for the Lewinian environment. A questionnaire is used to measure the Big Five personality dimensions as well as five dimensions of situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…Research on states has shown that the interaction between person and situation contributes substantially to the variance of trait assessments (e.g., Deinzer et al, 1995; Ziegler, Ehrlenspiel, & Brand, 2009). Thus, sophisticated measurement approaches as well as sophisticated modeling approaches are required to overcome this obstacle (Horstmann, 2015).…”
Section: Possibilities and Challenges For Psychological Assessmentmentioning
confidence: 99%
“…Research on states has shown that the interaction between person and situation contributes substantially to the variance of trait assessments (e.g., Deinzer et al, 1995; Ziegler, Ehrlenspiel, & Brand, 2009). Thus, sophisticated measurement approaches as well as sophisticated modeling approaches are required to overcome this obstacle (Horstmann, 2015).…”
Section: Possibilities and Challenges For Psychological Assessmentmentioning
confidence: 99%